A função textual : discursiva da hipotaxe adverbial no gênero resposta argumentativa - Calicchio, Fátima Christina (2014)
We aim in this paper to analyze how adverbial hypotaxis can contribute to the construction of argumentativeness of argumentative answer genre. We selected as the object of analysis the textual productions that were further evaluated by the examining board of candidates for the entrance exam of Summer 2011, State University of Maringa. Considering the theoretical panorama, of the functionalism, are investigated in this work the textual-discursive functions of adverbial clauses that function as guide value, transitional bridge, frame, focus, topical function among other functions in conjunction clauses that can contribute to the construction of argumentativeness genre of argumentative response. As a theoretical contribution, we combine studies of functionalist as Mann & Thompson (1988); Matthiessen & Thompson (1988) Rhetorical Structure Theory - RST, According to this theory, the rhetorical relations give coherence to the discourse, giving unity and allowing the producer to achieve its purposes with the text produced, that is, the theory is based on the principle that in the text, in addition to the explicit content , implied propositions emerge from the combination of text portions. Added to this approach: studies of Decat (1999, 2008, 2009, 2010), Neves (1999, 2000, and others) and postulations about genre according to the view of Bakhtin (2000).